Application of functionalized graphene in Li–O2 batteries. (8th January 2021) - Cui, Xinhang; Luo, Yani; Zhou, Yin; Dong, Wenhao; Chen, Wei
Abstract: Li–O2 batteries (LOB) are considered as one of the most promising energy storage devices using renewable electricity to power electric vehicles because of its exceptionally high energy density. Carbon materials have been widely employed in LOB for its light weight and facile availability. In particular, graphene is a suitable candidate due to its unique two-dimensional structure, high conductivities, large specific surface areas, and good stability at high charge potential. However, the intrinsic catalytic activity of graphene is insufficient for the sluggish kinetics of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in LOB. Therefore, various surface functionalization schemes for graphene have been developed to tailor the surface chemistry of graphene. In this review, the properties and performances of functionalized graphene cathodes are discussed from theoretical and experimental aspects, including heteroatomic doping, oxygen functional group modifications, and catalyst decoration. Heteroatomic doping breaks electric neutrality of sp 2 carbon of graphene, which forms electron-deficient or electron-rich sites. Oxygen functional groups mainly create defective edges on graphene oxides with C−O, C=O, and −COO−. Catalyst decoration is widely attempted by various transition and precious metal and metal oxides. These induced reactive sites usually improve the ORR and/or OER in LOB by manipulating the adsorption energies of O2, LiO2, Li2 O2, and promoting electron transportation of cathode. In addition, functionalized graphene is used in anode and separators to prevent shuttle effect of redox mediators and suppress growth of Li dendrite.